2022
DOI: 10.3389/fphar.2022.995559
|View full text |Cite
|
Sign up to set email alerts
|

Natural products for migraine: Data-mining analyses of Chinese Medicine classical literature

Abstract: Background: Treatment effect of current pharmacotherapies for migraine is unsatisfying. Discovering new anti-migraine natural products and nutraceuticals from large collections of Chinese medicine classical literature may assist to address this gap.Methods: We conducted a comprehensive search in the Encyclopedia of Traditional Chinese Medicine (version 5.0) to obtain migraine-related citations, then screened and scored these citations to identify clinical management of migraine using oral herbal medicine in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…The frequency analysis indicated that herbs gan cao , gui zhi , chuan xiong , fu ling , bai zhu , yan hu suo , ban xia , chen pi , bai shao and xiang fu , were widely utilised for migraine, which is similar to the findings of our previous research ( Lyu et al, 2020 ; Lyu et al, 2022a ; Lyu et al, 2022b ; Zhang et al, 2022 ). These herbs were reported to exhibit anti-migraine, anti-depression, neuroprotective, sedative-hypnotic and/or antiemetic actions, as summarised in Table 8 .…”
Section: Discussionsupporting
confidence: 86%
“…The frequency analysis indicated that herbs gan cao , gui zhi , chuan xiong , fu ling , bai zhu , yan hu suo , ban xia , chen pi , bai shao and xiang fu , were widely utilised for migraine, which is similar to the findings of our previous research ( Lyu et al, 2020 ; Lyu et al, 2022a ; Lyu et al, 2022b ; Zhang et al, 2022 ). These herbs were reported to exhibit anti-migraine, anti-depression, neuroprotective, sedative-hypnotic and/or antiemetic actions, as summarised in Table 8 .…”
Section: Discussionsupporting
confidence: 86%
“…Educational research has surfaced various funding initiatives. Among these are studies analyzing user behavior when requesting texts from the library loans [38], uncovering natural products and antimigraine nutraceuticals from extensive classical medical literature collections [39], and rule extraction from the scoring records of 2002 computer science students at the Mongolian University of Science and Technology [40].…”
Section: State Of the Artmentioning
confidence: 99%